Civilization & science: in conflict or collaboration? A Ciba Foundation symposium - Symposium on Civilization and Science: in Conflict or Collaboration? (1971 : London, England) (London) (Amsterdam ; New York : Associated Scientific Publishers, 1972., 1972)
vii, 227 pages ; 25 cm